2020
DOI: 10.1097/ijg.0000000000001705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Toric Intraocular Lens Implantation on Visual Acuity and Astigmatism Status in Eyes Treated With Microhook Ab Interno Trabeculotomy

Abstract: Précis: Use of toric intraocular lenses is a reasonable option for better visual outcomes when a combined minimally invasive glaucoma surgery (MIGS) and cataract surgery is performed in eyes with corneal astigmatism. Purpose: To assess the efficacy of toric intraocular lenses (IOLs) in combined cataract and MIGS, visual and refractive outcomes were compared between eyes implanted with nontoric and toric IOLs during microhook ab interno trabeculotomy tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…[16] Previously, reasons for SIA after LEC were reported to be a gap around the scleral flap [1], sinking of the limbus because of the tissue loss under the scleral flap [17], tissue contraction due to extensive scleral cautery [18], subconjunctival scarring [19,20], corneal steepening due to the compression of a bleb by eyelid [18], and postoperative hypotony. [4] Absence of these possible mechanisms explains the small SIA by iStent [9] and other goniotomy-related MIGSs procedures [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16] Previously, reasons for SIA after LEC were reported to be a gap around the scleral flap [1], sinking of the limbus because of the tissue loss under the scleral flap [17], tissue contraction due to extensive scleral cautery [18], subconjunctival scarring [19,20], corneal steepening due to the compression of a bleb by eyelid [18], and postoperative hypotony. [4] Absence of these possible mechanisms explains the small SIA by iStent [9] and other goniotomy-related MIGSs procedures [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The study design and methods for statistical analyses were followed our previous works that tested the the roles of toric IOLs during TMH [ 7 , 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bissen-Miyajima et al [41] showed that the post-operative visual outcomes (distance-corrected visual acuity, contrast sensitivity) of glaucoma patients following EDOF IOL implantation was almost comparable to those of normal eyes with the same IOLs implanted and were within normal ranges. Ichioka et al (2021) [46] investigated the effect of toric IOL implantation on visual acuity and astigmatism in 20 POAG eyes with a pre-existing corneal astigmatism of −1.5 D, following combined cataract surgery with micro-hook ab interno trabeculotomy. Post-operatively, the logMAR UCVA was significantly better in the toric group (toric, 0.07 ± 0.07; non-toric, 0.33 ± 0.30; p = 0.0020).…”
Section: Visual Acuitymentioning
confidence: 99%
“…Accordingly, minimal induction of astigmatism and less astigmatism-related decreases in the BCVA would be expected with the μ LOT procedure. Recently, toric IOLs have been implanted increasingly in patients with corneal astigmatism during both cataract surgery alone and combined microincision vitrectomy surgery and cataract surgery to achieve postoperative spectacle-free distance vision [ 7 , 8 ]; however, the use of toric IOL during MIGS is limited and far between in the literature [ 9 ], and the correcting astigmatism effect of toric IOL during combined MIGS is unclear.…”
Section: Introductionmentioning
confidence: 99%